Ameliorative Effect of Chlorophyllin on Oxidative Stress in Experimental Model of Diabetes - Abani K Patar,; Surya Bhan,; Donkupar Syiem,; Anupama Sharma, (International Journal of Phytomedicine, 2016)
The aim of this present study was to investigate the effect of chlorophyllin (CHL) on oxidative stress in Streptozotocine (STZ) induced diabetic mice. For the study, mice were divided into Group A: normal control, Group B: diabetic control, Group C: diabetic mice treated with the ascorbic acid, and Group D: diabetic mice treated with CHL. Levels of Reactive Oxygen Species (ROS), lipid peroxidation, protein carbonyl, superoxide dismutase (CuZn SOD &Mn-SOD), catalase (CAT), glutathione peroxidase (GPx), and glutathione reductase (GR) activities were examined in kidney and heart tissues of different experimental groups. Histological and ultrastructuralstudies were also carried out to evaluate any changes in tissues as well as sub-cellular organelles. ROS, lipid peroxidation, and protein carbonyl levels have been significantly decreased with concomitant increased of CuZn SOD, Mn-SOD, CAT, GPx, and GR activity in CHLtreated diabetic mice. The histological and ultrastructural studies showed that CHL attenuates the detrimental effect of oxidative stress and alleviated tissue injuries in STZ induced diabetic mice. These results suggested that CHL possesses antioxidative activity and has the potential to amelioratediabetes-associated oxidative stress in mice.